BaWO2F4: a mixed anion X-ray scintillator with excellent photoluminescence quantum efficiency. Issue 31 (29th July 2020) - Ayer, Gyanendra B.; Klepov, Vladislav V.; Smith, Mark D.; Hu, Ming; Yang, Zhonghua; Martin, Corey R.; Morrison, Gregory; zur Loye, Hans-Conrad
Abstract : Luminescence spectra of a new self-activated X-ray scintillator, BaWO2 F4, and the optical image of scintillating ground crystals when exposed to X-rays. Abstract : A new self-activated X-ray scintillator, BaWO2 F4, with an excellent photoluminescence quantum efficiency is reported. Hydrothermally grown single crystals, space group P 2/ n, exhibit a 3D framework structure containing isolated WO2 F4 octahedra. BaWO2 F4 exhibits green emission under UV light with a high quantum yield of 53% and scintillates when exposed to X-rays(Cu).